2006
DOI: 10.1097/01.hjh.0000239297.63377.3f
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan restores the in-vivo insulin signaling pathway leading to Akt activation in obese Zucker rats

Abstract: The present study provides substantial information that demonstrates that long-term selective AII blockade by irbesartan improves insulin signaling and is associated with decreased insulin receptor Ser994 phosphorylation in the liver of a representative animal model of the human metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 55 publications
(94 reference statements)
9
62
2
Order By: Relevance
“…In accordance with our previous reports (Coba et al 2003, Muñoz et al 2006, IR Ser994 phosphorylation was almost undetectable in the liver of LZR (Fig. 3).…”
Section: Degree Of Phosphorylation Of the Ir At Ser994supporting
confidence: 81%
See 3 more Smart Citations
“…In accordance with our previous reports (Coba et al 2003, Muñoz et al 2006, IR Ser994 phosphorylation was almost undetectable in the liver of LZR (Fig. 3).…”
Section: Degree Of Phosphorylation Of the Ir At Ser994supporting
confidence: 81%
“…irbesartan, IRB), on insulin sensitivity (Henriksen et al 2001, Shiuchi et al 2004, Muñoz et al 2006. In a previous study, we demonstrated that blockade of the AT1R with IRB leads to an improvement of the response to insulin at the early stages of the insulin signaling pathway in the liver of OZRs which correlates with a reduction of the phosphorylation of the IR at Ser994 (Muñoz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After insulin administration, Zucker fatty rats show a decreased phosphorylation of Akt in liver compared with the lean rats, which reflects local insulin resistance. 48 These suggest that periodontal inflammation in the obese rats leads to aortic insulin resistance.…”
Section: Periodontitis and Aortic Insulin Signaling D Ekuni Et Almentioning
confidence: 99%